Transcriptomic Profiling of Quinoa Reveals Distinct Defense Responses to Exogenous Methyl Jasmonate and Salicylic Acid - Oscar M. Rollano-Peñaloza; Sara Neyrot; Jose A. Bravo Barrera; Patricia Mollinedo; Allan G. Rasmusson (Plants)
Plant defense responses are mediated by hormones such as jasmonic acid (JA) and salicylic acid (SA). JA and SA are known to trigger a range of different defense responses in model plants but little is described in crops like quinoa. Here, we present the first molecular description of JA and SA signaling at the transcriptomic level in quinoa. The transcriptomes of quinoa cv. Kurmi seedlings treated with 100 µM methyl JA or 1 mM SA for 4 h were analyzed, using on average 4.1 million paired-end reads per sample. Quinoa plants treated with JA showed 1246 differentially expressed (DE) genes and plants treated with SA showed 590 DE genes. The response to JA included the induction of genes for the biosynthesis of JA (8/8 genes) and lignin (10/11 genes), and displayed a strong association with treatments with Trichoderma biocontrol agents. The SA treatment triggered the upregulation of genes for the biosynthesis of monoterpenoids and glucosinolates, both having defense properties. Overall, this suggest that JA and SA promotes the biosynthesis of lignin polymers and chemical defense compounds, respectively. Overall, the DE genes identified can be used as molecular markers in quinoa for tracking plant-hormone pathway involvements in defense responses.